Pengembangan Perangkat Uji Kemahiran Berbahasa Indonesia Berbasis Aplikasi Android Sebagai Media Penguatan Pembelajaran Bahasa Indonesia - Yulianti, Uki Hares; Puspito, Danang Wahyu (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2018)
The Indonesian nation is currently in a language crisis. This linguistic crisis must be addressed wisely. The purpose of this study is to describe, design, and determine the effectiveness of the Indonesian language proficiency test application based on Android as a medium to strengthen Indonesian language learning. The theory used is learning media, android, UKBI ranking, UKBI material. The method used is research and development. The data analyzed were (1) information about the level of product requirements, (2) Indonesian language proficiency test material, (3) expert assessment results, and (4) effectiveness test data or limited trials. The research instrument used was (1) needs analysis questionnaire, (2) expert testing instrument, (3) limited test instrument. The results of the study are aspects of the appearance and layout of Indonesian language proficiency test devices based on android applications as a medium of learning reinforcement obtain an average score of 79. The aspect of content and effectiveness of the Indonesian language proficiency test based on the android application as a medium for strengthening Indonesian language learning has an average score of 83.3 in the very good category.Keywords: application; Indonesian Language Proficiency Test (UKBI); based on android.